2017
DOI: 10.1111/jace.15194
|View full text |Cite
|
Sign up to set email alerts
|

BaO−B2O3 system and its mysterious member Ba3B2O6

Abstract: The first systematic study of the BaO-B 2 O 3 system and barium orthoborate Ba 3 B 2 O 6 (3BaOÁB 2 O 3 ) was reported in 1949. Thereafter, the system was repeatedly refined but the structure of Ba 3 B 2 O 6 compound has not been adequately studied yet. In our study we have, for the first time, obtained the crystalline samples of Ba 3 B 2 O 6 . The solved structure (Pbam, a = 13.5923(4) A, b = 13.6702 The studies of BaO-B 2 O 3 system are complicated by the high reactivity and hygroscopicity of melts. High visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…A different 8-fold oxygen coordination in our new crystal structure can be observed for the Ba4, Ba5 and Ba6 ions. This latter oxygen coordination was reported for Ba 3 (BO 3 ) 2 [22]. Also an octahedral anionic coordination is known for Ba (although an octahedral oxygen coordination is much more typical for somewhat smaller but still very large Sr 2+ ions) and has been reported for Ba 2 CuO 2 Cl [23].…”
Section: Structuresupporting
confidence: 68%
“…A different 8-fold oxygen coordination in our new crystal structure can be observed for the Ba4, Ba5 and Ba6 ions. This latter oxygen coordination was reported for Ba 3 (BO 3 ) 2 [22]. Also an octahedral anionic coordination is known for Ba (although an octahedral oxygen coordination is much more typical for somewhat smaller but still very large Sr 2+ ions) and has been reported for Ba 2 CuO 2 Cl [23].…”
Section: Structuresupporting
confidence: 68%
“…Therefore, it can be deduced that BaB 2 O 3 F 2 begins to decompose at about 610 °C. Meanwhile, there is a wide endothermic peak on the DSC curve beginning at 950 °C, which is consistent with the melting temperature of BaB 4 O 7 . In addition, the powder second harmonic generation (SHG) test of BaB 2 O 3 F 2 was carried out by the Kurtz–Perry method on Nd:YVO 4 solid‐state lasers (1064 nm) and no apparent SHG signal was observed.…”
Section: Crystal Data and Structure Refinement For Bab2o3f2mentioning
confidence: 53%
“…To further confirm the thermal behavior of BaB 2 O 3 F 2 ,i ts powder XRD patterns were recorded for the sample annealed at 550 and 850 8C, respectively.Ass hown in Figure 4a,t here are no significant changesf or the XRD patterns at 550 8Cc ompared to the calculated one. [14] In addition, the powder second harmonic generation (SHG) test of BaB 2 O 3 F 2 was carried out by the Kurtz-Perry method [15] on Nd:YVO 4 solid-state lasers (1064 nm) and no ap-parentS HG signal was observed. Therefore, it can be deduced that BaB 2 O 3 F 2 begins to decompose at about6 10 8C.…”
mentioning
confidence: 99%
“…The same cation pattern, Ba 12 (BO 3 ) 6 6+ , was identified in two complex fluoride borates, 24 namely, Ba 12 (BO 3 ) 6 [BO 3 ][LiF 4 ] and Ba 12 (BO 3 ) 6 [BO 3 ]-[NaF 4 ]. 20 We have grown optical-quality crystals from the composition BaO:BaF , has revealed that they crystallize in the noncentrosymmetric space group P4 2 bc, in contrast to the conclusion for the centrosymmetric space group I4/mcm. 23 The absence of inversion symmetry in a Ba 12 (BO 3 ) 6 [BO 3 ][(Li,Na)F 4 ] solid solution was confirmed by the observation of pyroelectric luminescence.…”
Section: ■ Introductionmentioning
confidence: 76%